CORRELATION OF AEROBIC EXERCISE PERFORMED IN DIFFERENT LENGTHS WITH PRESSURE ANSWERS OF HYPERTENSIVE SUBJECTS. (Fiep Bulletin - online, 2011)
Preface: It is consensus in the scientific literature that physical exercise, especially aerobic, is a very effective non-drug treatment of hypertension. This study seeks to identify whether the aerobic exercise performed for a longer period of time enhances the magnitude and / or the duration of post-exercise hypotension (PEH). Materials and Methods: Five (5) hypertensive volunteers (50.2 ± 5.3 years) have been analyzed for 22h in three non-consecutive days: control (CD), after a continuous session of 30 minutes (CE30) and after a session continuous of 60 minutes (CE60). Results: In the days when the group performed the exercise there was significant PEH presented the following values: up to 15.2 mmHg (CE30) and 24.4 mmHg (EC60) for SBP and 6.8 mmHg and 9.2 after CE30 mmHg after the CE60 for DBP. Discussion: According to the results, the longer exercise session provided a higher magnitude of PEH in relation to the shorter exercise. Conclusion: Aerobic exercise per 60 minutes enhances the magnitude of the PEH compared to 30 minutes, but provides no additional effect on its duration.
Keywords: Hypertension; aerobic exercise; post exercise hypotension; magnitude; length